160 TLR9-activated B cells imprint adoptively transferred CD8+ T cells with potent tumor immunity and persistence in vivo. (9th November 2020) - Smith, Aubrey; Knochelmann, Hannah; Wyatt, Megan; Dwyer, Connor; Rivera, Guillermo Rangel; Reyes, Amalia Rivera; Thaxton, Jessica; Bartee, Eric; Rubinstein, Mark; Liu, Bei; Paulos, Chrystal
Abstract : Background: Compared to traditional therapies for advanced malignancies, adoptive T cell transfer (ACT) therapy has increased the number of patients who achieve complete regressions; however, only about 20% of patients achieve lasting progression-free survival. Thus, more potent cell therapies for cancer are urgently needed. Preconditioning patients with chemo- or radiotherapy prior to cell transfer provides several benefits to the transferred T cells. One of these benefits is activation of the host immune system Toll-like receptors (TLRs) via microbes leaked from the injured gut. Direct administration of TLR agonists has been used in numerous preclinical and clinical trial settings, but has shown toxicity and limited success in promoting tumor immunity in patients. We hypothesized that TLR agonists could be used in an alternative way – in the ex vivo propagation of potent T cells for ACT. Methods: To test our hypothesis, we employed the pmel-1 ACT model, where all CD8+ T cells express a transgenic TCR which recognizes the gp100 epitope expressed by melanoma. To determine if TLR agonists could improve cell therapy, we activated CD8+ T cells in the presence of APCs and the TLR9 agonist, CpG, and transferred T cells to B16F10 melanoma-bearing mice. Results: Pmel-1 CD8+ T cell products expanded with CpG elicited potent anti-melanoma immunity in vivo and improved survival compared to traditionally expanded T cell therapy. CpG-derived T cells engrafted robustly and persisted longer than traditional T cells in the host. We explored the characteristics of CpG-expanded T cells and found that T cells generated from a CpG culture incur a unique proteomic and cell surface signature phenotype. Of all the cell types present in the starting culture (CD4+ T cells, NK cells, B cells, DCs, macrophages), B cells were the only cell type critical to achieve a more potent T cell therapy with CpG. In a direct comparison of CpG class A (targeting DCs) and CpG class B (targeting B cells), only the B cell-activating CpG improved cell therapy. Finally, we found that B cells alone could improve purified CD8+ T cells for ACT when the co-culture was activated with CpG, indicating that B cells become potent APCs in this context. Conclusions: Collectively, our findings indicate a novel way to use TLR agonists to improve ACT and reveal a critical role for B cells in the expansion of potent anti-tumor CD8+ T cells. Translating these findings to ACT therapies could provide dramatic improvements in patients with late stage malignancies. Acknowledgements: Proteomic analysis was performed at the Mass Spectrometry Facility, a University Shared Research Resource at the Medical University of South Carolina, using instrumentation acquired through the NIH shared instrumentation grant program (S10 OD010731-Orbitrap Elite Mass Spectrometer or Orbitrap Fusion Lumos ETD/UVD MS (S10 OD025126). Trial Registration: NA Ethics Approval: All animal procedures were approved by the Institutional Animal Care & Use Committee of the Medical University of South Carolina, protocol number 0488. Consent: NA References: NA